THE RELATIONSHIP BETWEEN CONSENT AND ANXIETY IN PATIENTS WITH FEMUR FRACTURES AT RADEN MATTAHER HOSPITAL - Saniatul Mabruroh; Indah Mawarti; Luri Mekeama (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Femoral fractures are musculoskeletal injuries that often require operative treatment. Before undergoing surgery, patients generally experience anxiety due to limited understanding of the procedure, risks, and outcomes of surgery. Proper implementation of informed consent procedures by healthcare professionals is considered to improve patient understanding and potentially reduce anxiety levels. This study aims to determine the relationship between the implementation of informed consent procedures and the preoperative anxiety levels of femoral fracture patients at Raden Mattaher Regional General Hospital in Jambi. This study used a quantitative approach with a cross-sectional design. A sample of 75 respondents was selected through a total sampling technique. Data collection used an informed consent questionnaire and the Hamilton Anxiety Rating Scale, which were then analyzed using the Spearman Rank correlation test. The results showed that the majority of informed consent implementation was in the adequate category (65.3%), while the anxiety level was predominantly in the severe category (44.0%). Statistical analysis obtained a p-value of 0.000, indicating a significant relationship between the implementation of informed consent procedures and the preoperative anxiety levels of femoral fracture patients.